1999
DOI: 10.1074/jbc.274.30.21078
|View full text |Cite
|
Sign up to set email alerts
|

Novel Messenger RNA and Alternative Promoter for Murine Acetylcholinesterase

Abstract: A portion of the 5-flanking region of murine acetylcholinesterase was cloned from genomic DNA by 5-rapid amplification of genomic ends, identified in a mouse genomic library, and sequenced. Multiple potential binding sites for universal and tissue-specific transcription factors were suggestive of a promoter region within this DNA sequence. Potential promoter activity was confirmed by coupling the new sequence to the open reading frame of a luciferase reporter gene in transient expression experiments with nerve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…This result is consistent with recent studies indicating that high levels of cyclic AMP stimulate the synthesis of AChE in avian myotubes (Choi et al, 1998). Moreover, cyclic AMP responsive element (CRE) sequences were found either in mouse (Atanasova et al, 1999) or human AChE genes (Ben Aziz-Aloya et al, 1993). Similarly, the human and chick AChE gene promoters were shown to be activated by cyclic AMP-dependent pathway (Wan et al, 2000;Choi et al, 2000), suggesting the involvement of CRE in mammals and avian AChE transcription.…”
Section: Discussionsupporting
confidence: 80%
“…This result is consistent with recent studies indicating that high levels of cyclic AMP stimulate the synthesis of AChE in avian myotubes (Choi et al, 1998). Moreover, cyclic AMP responsive element (CRE) sequences were found either in mouse (Atanasova et al, 1999) or human AChE genes (Ben Aziz-Aloya et al, 1993). Similarly, the human and chick AChE gene promoters were shown to be activated by cyclic AMP-dependent pathway (Wan et al, 2000;Choi et al, 2000), suggesting the involvement of CRE in mammals and avian AChE transcription.…”
Section: Discussionsupporting
confidence: 80%
“…We identified a canonical TATA box that contrasts with other cholinesterase genes that are devoid of this regulating element. However, a TATA box has been identified in the recently described murine AChE neuronal promoter (51). A TATA repeat was also found 32 bp upstream from the Torpedo AChE transcription start site.…”
Section: Discussionmentioning
confidence: 99%
“…Early Expression of mRNAs and Protein in Embryos-Tissue specificity and early expression of cholinesterases in mammals are due to specific transcription factor binding sites (50), alternative promoter usage (51), and intronic enhancers (52,53). In the zebrafish ache 5Ј non-coding region and first intron, no homology was detected with other ache genes.…”
Section: Discussionmentioning
confidence: 99%
“…Two proximal human (18) and mouse (7,8) ACHE promoters have been described previously. In our current study we demonstrate that human and mouse ACHE genes contain at least four alternative first exons each of which at least one encodes an extended N terminus.…”
Section: Discussionmentioning
confidence: 99%
“…AChE pre-mRNA is subject to stimulus-induced 3Ј alternative splicing (6), and previous evidence has suggested that it is also subject to alternate promoter usage (7,8). We analyzed the genomic regions flanking the human and mouse ACHE genes and found an unexpected, evolutionarily conserved diversity of alternate exons at their 5Ј end.…”
mentioning
confidence: 99%